2003
DOI: 10.1001/archderm.139.12.1620
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Melanomas Associated With Nevi

Abstract: To determine the frequency of and the histologic and clinical factors associated with melanoma existing in histologic contiguity with a nevus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
165
1
16

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(198 citation statements)
references
References 28 publications
(51 reference statements)
14
165
1
16
Order By: Relevance
“…Our observed prevalence of contiguous neval remnants in approximately half of all SSM but only 11% of LM/LMM is similar in magnitude to previously reported estimates. [10][11][12][13][14][15] Because of these marked differences by histologic type, we restricted further analyses to melanomas of the superficial spreading type. We found that SSM of the H & N was significantly less likely than SSM of the back to be associated with a contiguous nevus in accord with earlier descriptive studies of the anatomical distribution of nevusassociated melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our observed prevalence of contiguous neval remnants in approximately half of all SSM but only 11% of LM/LMM is similar in magnitude to previously reported estimates. [10][11][12][13][14][15] Because of these marked differences by histologic type, we restricted further analyses to melanomas of the superficial spreading type. We found that SSM of the H & N was significantly less likely than SSM of the back to be associated with a contiguous nevus in accord with earlier descriptive studies of the anatomical distribution of nevusassociated melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The concordant findings from descriptive and analytical studies are consistent with melanomas at different body sites arising through different pathways, but do not shed light on the mechanisms of pathogenesis. To address this issue, investigators have systematically appraised histological features and noted that melanomas arising from a benign melanocytic nevus differ from those arising de novo, being more frequent on the trunk than the head and neck, and being associated with young age and high nevus counts [20][21][22][23]. These congruent findings point to one group of melanomas arising through a high-nevus/low-sunlight pathway (predominantly on the trunk) and another group of mainly head and neck melanomas arising through a low-nevus/high-sunlight pathway.…”
Section: David C Whitemanmentioning
confidence: 99%
“…8 However, the best evidence for this association is the histological recognition of dysplastic nevi in contiguity with a melanoma, which is observed in about 20-40% of cases in most studies. [12][13][14][15][16][17] Thus, the majority of melanomas do not arise in association with a demonstrable nevus. The prevalence of dysplastic nevi is vastly greater in populations than that of melanoma, indicating, consistent with clinical observations, 18 that most dysplastic nevi are stable and do not progress to melanoma.…”
Section: Dysplastic Nevimentioning
confidence: 99%